Differential Training Tasks Trigger the Decrease of Concatenation between Cardiovascular Parameters - Deivydas Velička; Gilija Bernotienė; Kristina Poderienė; Alfonsas Vainoras; Jonas Poderys (Lithuanian Sports University, 2018)
Background. A lot of studies have shown the Differential Training (DT) is more effective than the traditional training based on repetition at constant conditions. The aim of this study was to find the changes in dynamical concatenation between ECG parameters during the DT task. Methods. Participants (13 healthy adult males) performed two balance tests standing on LIBRA balance board. Continuous ECG registration during both balance tests and during the rest was 3 minutes. The changeable parametric interactions and its dynamics during exercise tasks while monitoring ECG parameters and its data sequences analysis based on mathematical method based on matrix theory were applied, the concatenation between ECG parameters were analysed. Results. Results obtained during the study showed that there were no drastic differences between ECG parameters while performing both balance tests. The concatenation between analysed ECG parameters increased or there was no significant change. The decrease of concatenation was observed during the second task while the participants performed the squats standing on the balance board. This type of change in concatenation was found during the analysis of all ECG parameters, i.e. between duration of RR intervals and QRS, between JT and RR intervals and between QRS and JT intervals. Conclusion.  DT  tasks  trigger  the  decrease  of  concatenation  between  cardiovascular  parameters  that  allows discussing about the hypothesis that decrease of concatenation between systemic regulatory commands and cardiac metabolic changes could be one of possible chain activating and enhancing the efficiency of long-term adaptation at conditions of DT. Keywords:  cardiovascular system, concatenation, Differential Training.